Households neighboring wildlife protected areas may be at a higher risk of rabies than those located further away: a community-based cross-sectional cohort study at Pian Upe game reserve, Bukedea district, Eastern Uganda - Atuheire, Collins G. K.; Okwee-Acai, James; Taremwa, Martha; Ssajjakambwe, Paul; Munyeme, Musso; Kankya, Clovice; Terence, Odoch; Ssali, Sarah N.; Mwiine, Frank N.; Buhler, Kayla J.; Tryland, Morten (Frontiers in Tropical Diseases, 2024)
Introduction: This study examines rabies incidence and associated risk factors at the interface between wildlife and human communities near Pian-Upe game reserve in Eastern Uganda. We hypothesized that human settlements in closer proximity to the reserve would exhibit higher rabies risk compared to those located further away.Methods: Using a standard questionnaire, households within <4, 4-14, and >14 km from Pian Upe game reserve in Bukedea District were interviewed. Data on socio-demographic characteristics, recent rabid animal bites, and suspected human and livestock rabies cases for the past one year were collected after seeking informed consent. Descriptive statistics were used to analyze socio-demographic information and incidence data, while separate Generalized Linear Models for binomial family under log-link function were used to regress predictors of rabies incidence and mortality.Results: Between January and March 2023, 302 participants were interviewed.Respondents had an average age of 44 years, with females comprising 34% of the sample. All households (100%) owned at least one dog with only 47% having vaccinated their dogs in the past year. Additionally, 39% of respondents used dogs for hunting game animals. Rabies incidence increased with distance to the game reserve, raising from 7.5 to 15.7% among humans and dogs, and from 5.0 to 9.8% among livestock every year.Significant factors associated with rabies in humans included primary education level (aRR=3.8, 95%CI 1.0-23.7) and grazing livestock in the reserve (aRR=5.30, 95%CI 1.0-40.3). Mortality was associated with fetching firewood from the game reserve (aRR=4.7, 95%CI 1.3-17.5).This study reveals an increased risk of rabies as households approach the game reserve. To prevent the spread of rabies, we recommend community sensitization and targeted dog vaccination in settlements surrounding game reserves.